1989
DOI: 10.5547/issn0195-6574-ej-vol10-no3-10
|View full text |Cite
|
Sign up to set email alerts
|

Fuelwood Use in Urban Areas: A Case Study of Raipur, India

Abstract: Concern over deforestation in developing countries has led to increased interest in fuelwood markets, particularly the major market in cooking fuels for urban populations. This case study of Raipur, India, examines the use of cooking fuels by households and small commercial users, with emphasis on the role of fuelwood. It finds that total cooking energy consumption per household (in Btus) is relatively constant over a wide range of household income. However, the composition of fuel supplies varies with income,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The remaining studies found fuelwood to be an inferior good with income negatively related, and price positively related, to demand. The results of three studies (Dunkerley et al, 1990;Hughes-Cromwick, 1985;Macauley et al, 1989) suggest that fuelwood is inferior, but modern fuels are superior.…”
Section: Previous Fuelwood Demand Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…The remaining studies found fuelwood to be an inferior good with income negatively related, and price positively related, to demand. The results of three studies (Dunkerley et al, 1990;Hughes-Cromwick, 1985;Macauley et al, 1989) suggest that fuelwood is inferior, but modern fuels are superior.…”
Section: Previous Fuelwood Demand Studiesmentioning
confidence: 94%
“…The results also suggest that energy consumption increases slightly with income if household size is held constant. From a policy perspective, Macauley et al (1989) stress that household incomes must rise substantially before significant declines in average household fuelwood demand occur. Pachauri (1983) estimates household demand of both modern and traditional fuels in India by using time spent on the collection of traditional fuels, price of modern fuels, household income, and energy consumption.…”
Section: Previous Fuelwood Demand Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy alternatives for many urban populations are further restricted due to cost and inadequate infrastructure. For instance, Macauley et al (1989) showed that in India fuel wood accounted for about 33 per cent of total energy consumption and that fuel wood is negatively related to level of income while the regression equation has a positive coefficient on LPG use. However, with the removal of subsidy on LPG more higher income earners were returning to the use of traditional fuels.…”
Section: Urbanization and Energy Usementioning
confidence: 97%
“…Similarly, fuelwood consumption in establishments (restaurants, bakeries, hostels, rituals etc.) in urban areas was estimated by assuming the Raipur rate (Macauley et al 1989) of fuelwood use to be valid for all towns with a population of less than 1 million, and Hyderabad-type use (Alam et al 1985) for a population of more than 1 million. This gave a national estimate of 10 million t of fuelwood used in urban establishments.…”
Section: Sampling Design and Methodology For Consumptionmentioning
confidence: 99%